Elder Abuse in Rural & Remote Communities: Social Policy, Prevention and Responses - Warren, Amy; Blundell, Barbara (Curtin University and OPAN, 2018)
Elder abuse prevalence in rural and remote communities is thought to be similar to that of urban areas. However, factors such as geographic isolation, service and support limitations, and issues around privacy and confidentiality may hinder response efforts in these communities. This article reports the findings of an international scoping literature review focussed on social policy, prevention, and service responses to elder abuse in rural and remote communities. Through literature scoping, stakeholder consultations, and three rounds of screening, 47 articles were identified for inclusion in the review. Four Australian elder abuse policy documents, and 14 types of prevention or service responses were identified in the literature, including several Indigenous-specific initiatives. The review highlighted the need for meaningful inclusion of rural and remote communities in elder abuse policy, as well as the importance of community consultation and consideration of the local context in developing prevention and responses for these communities.